Slum upgrading: Can the 1.5 °C carbon reduction work with SDGs in these settlements? - Teferi, Z.; Newman, Peter (Cogitatio, 2018)
The need to improve slum housing is a major urban planning agenda, especially in Africa and Asia. This article addresses whether it seems feasible to do this whilst helping achieve the 1.5 °C agenda, which requires zero carbon power along with enabling the Sustainable Development Goals. Survey data from Jakarta and Addis Ababa on the metabolism and liveability of slums are used to illustrate these issues. The article shows that this is possible due to advances in community-based distributed infrastructure that enable community structures to be retained whilst improving physical conditions. The urban planning implications are investigated to enable these ‘leapfrog’ technologies and a more inclusive approach to slums that enables in situ redevelopment instead of slum clearance, and which could be assisted through climate financing.